Research Status and Key Technologies of Electromagnetic Catapult Technology for Shipboards - Liu, Hongbo; Li, Shuxin; Li, Yuheng; Yang, Xiaodong (Recent Patents on Engineering, 2024)
<span class=
Keywords: orbital electromagnetic catapult technology